Immunomodulatory Potential of Leptadenia arborea in Immune-Challenged Rats - Abdoon, Iman Hassan; Parveen, Bushra; Osman, Bashier; Mohamed, Mona S; Osman, Wadah JA; Ahmad, Sayeed (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Plant-based remedies play a crucial role as powerful health aid worldwide. In recent years, the usage of complementary and alternative medicines has grown rapidly. The objective of the present study was to evaluate the immunomodulatory effects of methanolic extract of Leptadenia arborea leaves in BCG-immunized rats. Materials and Methods: L. arborea extract suspended in 1% carboxymethyl cellulose (CMC) was administered in three doses viz 50, 100 and 200 mg/kg, p.o. All animals were challenged with 0.05 ml BCG, sc on day 0. Levamisole (18 mg/kg body weight; p.o.) was used as a positive control group. Results: L. arborea extract exhibited a significant dose- and time-dependent increase in the plasma levels of IFN-γ and TGF-β. On day 14, plant's extract significantly increased TNF-α level at dose 200 mg/kg. Moreover, L. arborea extract elicited an inhibitory effect on IL-10 levels that was significantly observed at dose 200 mg/kg of the plant extract. LD50 value was calculated to be 15.5 g/kg body weight and the extract didn't display any behavioral changes or clinical signs after 12 hr of treatment. Conclusion: L. arborea methanol extract showed immunostimulatory effects through elevation of IFN-γ and thereby activation of cell-mediated immunity.
Keywords: Leptadenia arborea; Cell-mediated immunity; TH1 cytokines; TH2 cytokines; Immunomodulator